2002
DOI: 10.1177/039139880202500408
|View full text |Cite
|
Sign up to set email alerts
|

The α1-antitrypsin/elastase Complex as an Experimental Model for Hemodialysis in Acute Catabolic Renal Failure, Extracorporeal Blood Circulation and Cardiocirculatory Bypass

Abstract: A modified polyethersulphone graft membrane was loaded with antiproteases, with the aim of reducing the active protease blood concentration during hemodialysis in acute catabolic renal failure or cardiopulmonary bypass. As protease/antiprotease system, elastase and alpha1-antitrypsin were used. The concentration of active elastase in aqueous solutions decreased as function of contact time with the membrane, approaching saturation. A 40% loss of elastase activity was obtained at pH 7.4, which was not due to aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…More recently (4, 5) it has been demonstrated that it is possible to reduce the concentration of active elastase in an aqueous solution interacting with a modified polyethersulfone membrane loaded with α 1 ‐antitrypsin. Elastase was chosen as protease model, because it represents one of the main proteolytic enzymes released during HE or CPB (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…More recently (4, 5) it has been demonstrated that it is possible to reduce the concentration of active elastase in an aqueous solution interacting with a modified polyethersulfone membrane loaded with α 1 ‐antitrypsin. Elastase was chosen as protease model, because it represents one of the main proteolytic enzymes released during HE or CPB (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…An externally applied field magnetizes the parallel wires which, in turn, generate sufficient local magnetic field gradients within each tubing segment to quantitatively capture the blood-borne magnetic spheres at the inner tubing wall. This biomedical design borrows from and combines two established technologies: first, the high gradient magnetic separation (HGMS) principle, commonly utilized in industry for the separation of waste products [19][20][21] and biomolecule and cell separations [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and second, the biomedical application of extracorporeal blood circulation [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…More recently (4,5) it has been demonstrated that it is possible to reduce the concentration of active elastase in an aqueous solution interacting with a modified polyethersulfone membrane loaded with R 1 -antitrypsin. Elastase was chosen as protease model, because it represents one of the main proteolytic enzymes released during HE or CPB (6,7).…”
Section: Introductionmentioning
confidence: 99%